RE-EVALUASI PENDIRIAN BANK DIGITAL DI INDONESIA: PARADIGMA, KONSEP DAN REGULASI - Dewantara, Reka; Sitorus, Hany Ayunda Mernisi (Veritas et Justitia, 2022)
The Financial Services Authority, anticipating the movement towards digital (bank 5.0), issued Regulation no. 12/POJK.03/2021 concerning Commercial Banks. However, its coverage is limited. It covers only rules on how to establish and manage digital branches of existing banks. Not yet available are special arrangements for the establishment of digital commercial banks or neo-banks. This paper discusses the possibility of establishing digital banks in Indonesia. By perusing the prevailing laws and regulations, and re-evaluate what exist, the author reached the conclusion that the Bank Law should be changed to accommodate this new trend. The prevailing OJK regulation apparently does not suffice as the legal basis for the establishment and operation of digital system of the Bank-Ied model, the Telco-Ied Model or the Hybrid Model, or neo-bank. In addition, adequate arrangements are needed regarding online dispute resolution, and imposition of sanctions.